Comparison between clinical-ultrasound and pathological tumor size in breast cancer. Descriptive study - Bonilla Sepúlveda, Oscar Alejandro (2025)
Introduction: Clinical evaluation of tumor size in the TNM classification is an integralpart of the diagnosis of breast carcinoma. The surgical decision depends largely on the clinical stage. Objective: To determine the concordance between the clinical-ultrasound and pathological size of invasive breast carcinoma. Materials and methods: Observational, retrospective study. Surgical pathology and ultrasoundreports of patients with invasive breast carcinoma were reviewed. Data from 271cases were included. Concordance was defined as a size difference equal to orless than 5 mm. Demographic and clinical data were collected and analyzed usingdescriptive statistics. Results: Concordance between clinical and pathologicaltumor size was 30.8% (n: 73), and ultrasound was 52.9% (n: 18). The mean clinicalsize was 33 mm (SD: 17.4), ultrasound was 11.3 mm (SD: 6.8) and pathological was22.2 mm (SD: 14.4). The Student t test showed a significant difference in clinicalmeasurement (t= 7.5 mm, 95% CI 7.33 - 12.5; p: 0.000), Pearson correlation (r: 0.224;p: 0.001) and ultrasound measurement (t: 3.83 mm, 95% CI 2.27 - 7.40; p: 0.001),Pearson correlation (r: 0.342; p: 0.048). There were significant clinical-pathologicaldifferences by clinical stages. Conclusions: In the sample studied, it was found thatthe clinical and ultrasound measurement of tumor size had a low correlation withthe pathological tumor size, clinically there was a tendency to overestimate andultrasound to underestimate, affecting the clinical classification (TNM) for tumor size.